Wanprestasi Pelaku Usaha Atas Hadiah Dalam Jual Beli Online - Rajalabis, Madeline A; Laturette, Adonia Ivonne; Kuahaty, Sarah Selfina (Faculty of Law Universitas Pattimura, 2024)
ABSTRACT: Default is an act that violates an agreement between two parties. If neither party is able to fulfill its obligations arising from the existing contract, such action may be considered a breach of contract. This is regulated in Law Number 8 of 1999 concerning Consumer Protection and Law Number 11 of 2008 concerning Electronic Information and Transactions. The research method used in this research is normative research carried out using a statutory approach and a conceptual approach. The sources of legal materials used are primary, secondary and tertiary legal materials. The technique for collecting legal materials in this research is by reading and reviewing various kinds of literature related to the research problem and directly related to the problem being studied. Based on the results of this research, consumers have the right to claim losses in buying and selling transactions for the promised gifts which are not fulfilled, so consumers have the right to make a claim for the promised gifts, because the promised gifts did not reach the buyers. Forms of legal protection for buyers against default are divided into two. Namely, preventive and repressive